2010
DOI: 10.5171/2010.303855
|View full text |Cite
|
Sign up to set email alerts
|

E-business Maturity and Information Technology In Portuguese SMEs

Abstract: The latest technological advances made over recent times led to a profound market change, characterized by increased competition. In order to be competitive, organizations have been forced to adapt themselves to this new reality, seeking innovative solutions permitting them to achieve lower costs, greater productivity and differentiation from competition.This work focuses the e-business maturity stages of Portuguese small and medium enterprises (SMEs). Our goal is to identify in which e-business maturity stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Comparing with the SMEs in developed countries, this condition is certainly still far behind. However, if it is compared with other developing countries, such as, Brazil, Malaysia, Portugal and South Africa, a similar condition is commonly found (Gonçalves et al 2010;Lin and Lee 2005;Molla and Licker 2004;Tigre 2003).…”
Section: Analysis and Discussionmentioning
confidence: 86%
“…Comparing with the SMEs in developed countries, this condition is certainly still far behind. However, if it is compared with other developing countries, such as, Brazil, Malaysia, Portugal and South Africa, a similar condition is commonly found (Gonçalves et al 2010;Lin and Lee 2005;Molla and Licker 2004;Tigre 2003).…”
Section: Analysis and Discussionmentioning
confidence: 86%
“…Stages of growth models have been used by researchers [8] [9], to explain the phases of maturity that organisations go through as they use and manage their information systems to facilitate their business activities [9]. Researchers have suggested that these models can be useful for providing a roadmap for improvement [10].…”
Section: Stages Of Growth Modelsmentioning
confidence: 99%
“…Researchers have suggested that these models can be useful for providing a roadmap for improvement [10]. Maturity models have been extended to include e-business [8] [10] [11] and Business to Business [12]. It is beneficial for companies to understand the holistic process of e-commerce implementation in order to be better able to plan and develop the organisations information system strategy.…”
Section: Stages Of Growth Modelsmentioning
confidence: 99%
“…Based on the results above, we can conclude that the digital economy is a reality in Portugal, not just for large enterprises but also for Portuguese SMEs, with a clear evolution in the maturity of the e-business (Morais et al, 2009), (Gonçalves et al, 2010).…”
Section: Evolution Of the E-business Maturity In Large Enterprisesmentioning
confidence: 99%